Prostatic arterial embolization as a micro-invasive treatment option for benign prostatic obstruction: A subtle balance between short-term follow-up patient-reported outcomes and de-obstructive effectiveness - Bertolo, Riccardo; Cipriani, Chiara; Giuliani, Maria Silvia; Maiorino, Francesco; Vittori, Matteo; Carilli, Marco; Signoretti, Marta; Minucci, Sergio; Bove, Pierluigi (Frontiers in Urology, 2022)
Purpose: To evaluate the effectiveness of prostatic arterial embolization (PAE) in the relief from benign prostatic obstruction (BPO) beyond the patient-reported outcomes. Methods: Retrospective evaluation of patients who underwent PAE (Mar 2015 – Dec 2019). All patients underwent prostate MRI to assess prostate volume (PVol), uroflowmetry to assess Qmax and were administered IPSS + QoL. 3 months postoperatively, MRI, and IPSS were repeated. Patients were contacted for urological consultation including uroflowmetry with post-voiding residual volume (PVR), IPSS + QoL. In addition, patient satisfaction was assessed. Sexual function including ejaculation and complications were recorded. Results: Fifty-two patients were analyzed. At baseline, PVol was 66 ml (IQR 48-67), Qmax 13.5 ml/s (IRQ 11.5-19), IPSS 23 (IQR 18-25) and QoL 4.5 (IQR 4-5). At 3-months follow-up, MRI showed a 27% (IQR 18-36) reduction in PVol (p<0.001). IPSS decreased by 81% (IQR 58-91, p < 0.001). At a median follow-up of 14 months (IQR 10.5-27.5), IPSS decreased by 40% (IQR 26-54, p < 0.001) and QoL by 50% (IQR 20-75, p = 0.002) versus baseline. Absolute Qmax was 12.2 ml/s (IQR 9.5-14). Median %variation of Qmax vs baseline was -7.3% (IQR -33.9; +25.5, p = 0.7). All sexually-active patients maintained ejaculation. 38 (73%) were satisfied with treatment received. One patient reported post-operative erectile dysfunction. All patients who were counseled for adjuvant endoscopic treatment refused surgery except by one. Conclusion: In our analysis PAE provided significant improvement in the short-term follow-up patient-reported outcomes. Most patients were satisfied, and ejaculation was maintained. On the other hand, effectiveness of PAE on the relief of BPO seemed virtually intangible in most of the cases.